Clinical Evaluation and Management of Finger Crush Injury - Jean Kharismatik Persada; Iwan Hipsa Achmad; Riza Aprizal (Jurnal Impresi Indonesia, 2025)
Hand injuries are among the most common musculoskeletal traumas and may lead to functional impairment, long-term disability, or limb loss if not properly managed. Among these, crush injury is a severe type characterized by damage to bones, soft tissues, and neuromuscular structures, often resulting from occupational accidents. This case report describes the diagnosis, management, and outcome of a 64-year-old male who presented to the Emergency Department of RSUD dr. Slamet Garut with severe pain and an open wound on his left hand after being struck by a concrete block. Data were obtained through anamnesis, physical examination, laboratory tests, radiography, and medical record review, then analyzed descriptively with reference to relevant literature. Ethical approval and informed consent were obtained. Examination showed an open wound, deformity, bleeding, and limited motion in the fourth and fifth digits of the left hand. Radiography revealed fractures of the distal phalanges. Due to extensive tissue damage and signs of ischemia, amputation of the distal phalanx of both digits was performed. The patient had a history of hypertension but no diabetes mellitus or other chronic diseases. He was diagnosed with a crush injury of the distal phalanges of the left hand caused by a work-related accident. Amputation was selected based on local tissue viability and long-term functional prognosis. Prompt diagnosis, appropriate management, and adherence to clinical guidelines are crucial to prevent complications and promote optimal recovery in crush injury cases.